Recovery from Strongyloides venezuelensis infection in Lewis rats is associated with a strong Th2 response - Chiuso-Minicucci, F. [UNESP]; Marra, N. M. [UNESP]; Zorzella-Pezavento, S. F. G. [UNESP]; Franca, T. G. D. [UNESP]; Ishikawa, L. L. W. [UNESP]; Amarante, M. R. V. [UNESP]; Amarante, Alessandro Francisco Talamini do [UNESP]; Sartori, Alexandrina [UNESP] (Wiley-Blackwell Publishing, Inc, 2010)
P>In this study, we investigated the characteristics of the infection and subsequent immunity induced by Strongyloides venezuelensis in Lewis rats. Animals were infected with 4000 L3 of S. venezuelensis and number of eggs per gram of faeces indicated an acute phase around day 8 and a recovery phase around day 32 after infection. A strong Th2 polarization during recovery phase was ascertained by a significant increase in IgG1 and IgE compared with that in the acute period. A shift in the cytokine profile confirmed these findings. A predominant production of IFN-gamma during the acute phase was followed by IL-10 production during recovery. Together these findings show that experimental infection of Lewis rats with S. venezuelensis presents a kinetics of parasite establishment and immunity similar to that described in other models of helminthic infection.
Keywords: Lewis rats; Strongyloides venezuelensis; Th2 cells